Lanzhou to Gwadar: The long road to global power - Banerjee, Gautam (Coleção Meira Mattos: revista das ciências militares, 2012)
The article has been published in magazine "South Asia Defence & Strategic Review"- Sep-Oct 12 issue. The development of Gwadar Port on Pakistan’s Makran Coast on the Arabian Sea has been in the news off and on since the project took a concrete shape in the late 1990’s. But thousands of kilometres to the North, across the entire length of Pakistan, then across the northern areas of the Indian state of Jammu & Kashmir currently occupied by Pakistan and finally, right up to the Western Province of Xinjiang in China, another development of monumental proportions had already taken place – the opening of the Karakoram Highway for commerce, in 1986. Both these Sino-Pak joint ventures, among two formally declared ‘all weather friends’, have generated considerable interest among strategists who focus on the South and West Asian region. However, it was only recently, following the turmoil that engulfs the region of Pakistan, Afghanistan and beyond, that the two apparently distinct events crystallized as parts of a grand design of immense geo-political implications, both encouraging and worrisome depending on which side the observer pitches for and as to how one is inclined to come to terms with it. This paper argues that development of the Karakoram Highway and the Gwadar Port had ever been but two ends of one strategic initiative to pave the way for China’s emergence as a world power. Further, it is argued that the overland ‘axis’, connecting China’s core areas, through her peripheral provinces, to the strategic outlet at the Gulf of Oman, is but a complimentary version of the sea connectivity between China, through the Indian Ocean and its littoral states, to West Asia and beyond to Africa – two arms of a strategic ‘jaw’, so to say.